Indexes of serial dynamometry for junior-footballers in the dynamics of correction of compensatory-adopting possibilities preparation of entsefabol - Марченко [Marchenko V.], Валерій Анатолійович; Малахов [Malakhov O.], О. В.; Сухарев [Sukharev S.], С. П.; Малахов [Malakhov V.], В. О. (Slobozhanskyi Herald of Science and Sport, 2012)
The problems of serial dynamometry are examined for junior-footballers in the dynamics of correction of scray adopting possibilities preparation of entsefabol. Authors are offer the use of features of serial dynamometry as models of some components of the functional loading with which sportsmen meet in the conditions of competition activity